2019
DOI: 10.1093/gji/ggz255
|View full text |Cite|
|
Sign up to set email alerts
|

Complex-conductivity monitoring to delineate aquifer pore clogging during nanoparticles injection

Abstract: SUMMARYLaboratory and field studies have demonstrated the applicability of nanoparticles (NP) for accelerated contaminant degradation. Beside other limitations (e.g. costs, delivery, longevity, non-target specific reactions), concerns of regulators arose regarding toxicity of injected NP and particles delivered off-target (i.e. renegade particles). Renegade particles also significantly reduce the efficiency of the remediation. The delivery of particles off-target is caused, mainly, by unintended fracking, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…Our review is research‐focused, but we note that opportunities exist for deployment of LTRM systems in the environmental consulting sector. One promising area is in monitoring environmental remediation processes to evaluate effectiveness of amendment delivery (Flores Orozco et al, 2019; LaBrecque, Miletto, et al, 1996; LaBrecque, Ramirez, et al, 1996) and its long‐term impact on subsurface biogeochemistry. Although not yet commercially available, the costs of low‐power LTRM systems, such as the system described in Figure 1, are significantly lower than conventional high‐power geophysical instruments on the market.…”
Section: Future Prospects and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review is research‐focused, but we note that opportunities exist for deployment of LTRM systems in the environmental consulting sector. One promising area is in monitoring environmental remediation processes to evaluate effectiveness of amendment delivery (Flores Orozco et al, 2019; LaBrecque, Miletto, et al, 1996; LaBrecque, Ramirez, et al, 1996) and its long‐term impact on subsurface biogeochemistry. Although not yet commercially available, the costs of low‐power LTRM systems, such as the system described in Figure 1, are significantly lower than conventional high‐power geophysical instruments on the market.…”
Section: Future Prospects and Challengesmentioning
confidence: 99%
“…Our review is research-focused, but we note that opportunities exist for deployment of LTRM systems in the environmental consulting sector. One promising area is in monitoring environmental remediation processes to evaluate effectiveness of amendment delivery (Flores Orozco et al, 2019;LaBrecque, Miletto, et al, 1996; and its long-term impact on subsurface biogeochemistry.…”
Section: Future Prospects and Challengesmentioning
confidence: 99%
“…The IP method was developed for the prospection of metallic mineral ores given the strong IP response in the presence of iron sulphides (Pelton et al, 1978). In recent years, IP has emerged as a promising method for various environmental and hydrogeological applications including the mapping of geochemical active zones (Flores-Orozco et al, 2020;Katona et al, 2021), the monitoring of changes in pore-space geometry accompanying bioremediation processes (Flores Orozco et al, 2011;Flores Orozco et al, 2019) and the assessment of permafrost degradation (Doetsch et al, 2015;Maierhofer et al, 2022), just to name a few. In the context of characterizing hillslopes affected by landslides, IP has revealed promising results (Flores Orozco et al, 2018a;Gallistl et al, 2018;Revil et al, 2020), as numerous laboratory studies reported a sensitivity of the IP method to soil-textural properties of the subsurface (Slater and Glaser, 2003;Tarasov and Titov, 2007;Revil and Florsch, 2010) and, thus, the improved estimation of hydraulic conductivity (Slater et al, 2014;Weller et al, 2015;Weller and Slater, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Commer et al ., 2011; Chen et al ., 2012; Orozco et al ., 2011, 2013) and monitoring chemical remediation through injection of micro to nanoscale iron (e.g. Slater and Binley, 2006a; Flores Orozco et al ., 2015 ; Flores Orozco et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%